Differential auditory brain response abnormalities in two intellectual disability conditions: SYNGAP1 mutations and Down syndrome. Issue 8 (August 2021) - Côté, Valérie; Knoth, Inga S.; Agbogba, Kristian; Vannasing, Phetsamone; Côté, Lucie; Major, Philippe; Michaud, Jacques L.; Barlaam, Fanny; Lippé, Sarah
Highlights: Human participants with SYNGAP1 mutations expressed less synchronization when processing an auditory stimulus. The Down syndrome group showed maintained synchronization. More gamma and beta power was found in subjects with SYNGAP1 mutations. Abstract: Objective: Altered sensory processing is common in intellectual disability (ID). Here, we study electroencephalographic responses to auditory stimulation in human subjects presenting a rare condition (mutations in SYNGAP1 ) which causes ID, epilepsy and autism. Methods: Auditory evoked potentials, time-frequency and inter-trial coherence analyses were used to compare subjects with SYNGAP1 mutations with Down syndrome (DS) and neurotypical (NT) participants (N = 61 ranging from three to 19 years of age). Results: Altered synchronization in the brain responses to sound were found in both ID groups. The SYNGAP1 mutations group showed less phase-locking in early time windows and lower frequency bands compared to NT, and in later time windows compared to NT and DS. Time-frequency analysis showed more power in beta-gamma in the SYNGAP1 group compared to NT participants. Conclusions: This study indicated reduced synchronization as well as more high frequencies power in SYNGAP1 mutations, while maintained synchronization was found in the DS group. These results might reflect dysfunctional sensory information processing caused by excitation/inhibition imbalance, or an imperfect compensatory mechanism in SYNGAP1 mutations individuals. Significance: Our study is the first to reveal brain response abnormalities in auditory sensory processing in SYNGAP1 mutations individuals, that are distinct from DS, another ID condition.